Charecterisation of Geothermal Resources at Kwako Hills in Zambia using magnetic and natural source audio-magnetotelluric - Chinamora, Blessing (My University, 2019)
The announcement by the Zambian government that geothermal energy will be recognized as an energy source in the 2013 national budget drew a lot of attention to investors and scientists. Since the 1950s reconnaissance geoscientific surveys have been carried out on geothermal targets in Zambia by the Geological Survey of Zambia (GSZ). The GSZ, together with an Italian company (DAL, SpA), studied various hot springs (Legg, 1974) and as a result, various prospects have been considered for development or exploration. In this research, the Kwako Hills prospect which is located near Mumbwa district, about 150 km northwest of Lusaka, hosts two hot springs which are good surface manifestations for geothermal energy potential was investigated for its geothermal energy reservoir potential using magnetic and natural source audio-magnetotelluric (NSAMT) geophysical methods. The focus of these surveys was on examining the structural controls that govern the occurrence of the hot springs and the outcropping Hook Batholith just to the north of the eastwest trending alluvium filled valley. The northern branch of the alluvium valley has a northwest–southeast trend which is the same as the minor fault controlling the two hot springs. These structural controls increase the vertical permeability in the area causing the thermal waters to circulate to depths where they acquire their heat. Permeability is high at intersections of faults and fracture zones, intersection of major and minor faults or intersection of faults and sedimentary aquifers. Major ENE and NE trending faults were mapped along the Mwembeshi Shear Zone and the boundary between the Hook Batholith and the Katanga sediments respectively. The area is underlain by foliated basement granitic gneiss, Hook Batholith granites and Katanga metasediments that are broken into fractures along the foliation trends that control the occurrence and flow of rivers and streams. Overlying the basement rocks are the recent Karoo and Kundelungu sediments which are also permeable along the bedding or cleavage planes. The vegetation pattern, flow and occurrence of rivers or streams reflect trends of zones of weakness in the basement. Fractured zones developed along these foliations and were mapped at outcropping scale using Google Earth, aeromagnetic and ground magnetic data interpretation. Interpretation of aeromagnetic data confirmed the foliation trends that were suggested by Abell (1970) and Naydenov et al. (2014). One dimensional (1D) and two dimensional (2D) magnetotelluric (MT) resistivity models were created on the basis of a 120 MT sounding data set. A dimensionality and distortion analysis of the NSAMT data was carried out based on the approach of Groom and Bailey (1989) and it was concluded that the data were collected almost perpendicular to iv strike, which is also supported by the geological mapping. MT smooth inversion models showed the lateral and vertical extent of the potential geothermal reservoir. Different 2D MT inversion approaches were applied to investigate the lateral continuity of the conductive sedimentary layer of the Kundelungu unit (slate, siltstone and shale). In order to map the subsurface structure of the area, a magnetic model was then produced using the acquired ground magnetic data and constrained using magnetic susceptibility measurements, MT data and geology mapped on the surface. Magnetic data interpretation confirmed an NW-SE fault controlling the hot springs, which was mapped using the NSAMT inversion results. The research shows that there is a lateral conductive, water saturated zone (reservoir) present between 150 m and 550 m depth and deeply seated faults in the basin. Along the deeply seated faults the conductive zones are vertical and continue with depth. The information shows that the thermal waters of the hot springs appear to circulate to depths more than 2.5 km along deep seated faults and foliation fractures penetrating the foliated rocks of the Hook Batholith and basement rocks. This water is heated by the regional geothermal gradient of 23ºC/km. Further exploration can be carried out on the study area to prove its potential for a geothermal resource.
A dissertation submitted to the Faculty Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Geophysics, Johannesburg, 2019